2020
DOI: 10.1186/s42506-020-00050-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of mother and newborn skin-to-skin contact in The Gambia: a secondary data analysis

Abstract: Background Skin-to-skin contact (SSC) between mother and the newborn brings many benefits including its potential to promote the survival of the newborn. Nevertheless, it is a practice that is underutilized in many resource-constrained settings including The Gambia where a high rate of maternal and child mortality has been reported. In this study, we examined the prevalence and determinants of mother and newborn SSC in The Gambia. Methods We used secondary data from The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 39 publications
8
30
2
5
Order By: Relevance
“…This study was conducted to assess skin-to-skin care practice and its associated factors among postnatal mothers who visit Gurage Zone public health centers; we found that 35.3% (95% CI; 31.3%-40.4%) of participants were practiced skinto-skin care to their newborn. The finding of this study was comparable with the studies conducted in Harar city, eastern Ethiopia 34.4%, 14 Gambia 35.7%, 15 and Brazil 37.5%. 17 The proportion of SSC practice in this study was higher than studies conducted in four regions of Ethiopia 25.8%, 18 Eastern India 15%, 7 and rural Ghana 10%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study was conducted to assess skin-to-skin care practice and its associated factors among postnatal mothers who visit Gurage Zone public health centers; we found that 35.3% (95% CI; 31.3%-40.4%) of participants were practiced skinto-skin care to their newborn. The finding of this study was comparable with the studies conducted in Harar city, eastern Ethiopia 34.4%, 14 Gambia 35.7%, 15 and Brazil 37.5%. 17 The proportion of SSC practice in this study was higher than studies conducted in four regions of Ethiopia 25.8%, 18 Eastern India 15%, 7 and rural Ghana 10%.…”
Section: Discussionsupporting
confidence: 90%
“…This difference was due to the difference in the distribution of health facilities where the distribution of health facilities in the study setting is found in urban areas whereas, in the Gambia, the health facilities are more distributed and found in rural area. 15 Mothers who had normal birth weight newborns (≥ 2500gm) were 3 times more likely to practice skin-toskin care than those mothers who had low birth weight newborns. This finding was consistent with the studies conducted in Gambia and Brazil.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Newborns were admitted to the study site from the EFSTH maternity unit (approximately 7,000 births per year) or from other hospitals or home with two thirds of admissions born outside EFSTH ( Okomo et al, 2015 ). At the time of this study in 2017, KMC was not practiced at EFSTH nor widely in The Gambia ( Ekholuenetale et al, 2020 ), although mothers were advised to provide skin-to-skin contact for 30 minutes immediately after feeding for clinically stable, small newborns. Small or sick newborns were cared for under radiant heaters or incubators, often with multiple occupancy, and with few nurses.…”
Section: Methodsmentioning
confidence: 99%